P305 Effectiveness and Safety of Vedolizumab in Biologic-Naïve Patients: Real-World Data from the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). (27th May 2021) - Macaluso, F; Fries, W; Renna, S; Viola, A; Muscianisi, M; Cappello, M; Guida, L; Siringo, S; Camilleri, S; Garufi, S; Privitera, A C; Belluardo, N; et al.
Abstract: Background: Biologic-naïve patients treated with Vedolizumab (VDZ) are largely underrepresented in real-world cohorts. We performed a multicentre, observational, cohort study on the effectiveness and safety of VDZ as treatment for Crohn's disease (CD) and ulcerative colitis (UC) among biologic-naïve subjects. Methods: Data of consecutive biologic-naïve patients with CD and UC treated with VDZ from July 2016 to December 2019 were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Disease (SN-IBD). The primary outcome was the clinical response at 14 and 52 weeks evaluated with Harvey Bradshaw Index in CD and partial Mayo score in UC. Results: 172 consecutive patients (CD: n=88; UC: n=84; median age 66.0 years) were included, with a median follow-up of 58.8 weeks. After 14 weeks, a clinical response was reported in 68.2% of patients with CD and 67.9% of patients with UC treated with VDZ, including 45.5% patients in the CD group and 46.4% patients in the UC group who achieved steroid-free remission. After 52 weeks, a clinical response was reported in 77.4% of CD and in 73.8% of UC patients treated with VDZ, including 59.7% patients in the CD group and 60.7% patients in the UC group who achieved steroid-free remission. All differences between CD and UC were not statistically significant. Cox survival analysis showed no significant difference in the probability of treatment discontinuation between CD and UC patients (log-rank p=0.73). Conclusion: This large, real-world, multicenter study demonstrated the effectiveness and safety of VDZ as a first-line biologic, showing high rates of clinical response and steroid-free remission at both induction and maintenance.